Major roads have important negative effects on insectivorous bat activity. (July 2019) - Claireau, Fabien; Bas, Yves; Pauwels, Julie; Barré, Kévin; Machon, Nathalie; Allegrini, Benjamin; Puechmaille, Sébastien J.; Kerbiriou, Christian
Abstract: The development of transportation infrastructure has been identified as one of the main pressures on biodiversity. The effects of transport infrastructure are more documented for terrestrial mammals, birds and amphibians than for bats. To assess the impacts of roads on bat activity, we carried out full-night acoustic recordings of bat calls at 306 sampling points at different distances from a major road at three study sites in France. To assess the relationship between bat activity and the distance to the major road, we performed generalized linear mixed model analyses for thirteen different species or groups and additionally explored the non-linear effect with generalized additive mixed models. Our results showed that low-flying species are more affected than high-flying species. Indeed, we found a significant negative effect of major roads on bat activity for the 'clutter-adapted' species, Eptesicus serotinus, Myotis spp., Pipistrellus pipistrellus and Rhinolophus hipposideros . These results demonstrate that the road-effect zone of major roads extends up to five kilometres. Extrapolating those road-effects zones to the major roads in the European Union, we estimated that 35% of the European Union is potentially negatively impacted. Finally, it seems urgent to consider these road effects with the cumulative effects of other roads by improving habitat connectivity and foraging areas in land use policies. Additionally, to implement drastic conservation practices for species of conservation concern in environmental impact assessment studies, efficient mitigation and offset measures implemented should be sized proportionally to the disturbance caused. Highlights: Major roads affect activity in five of the thirteen studied taxa. Low-flying species are more affected than those that fly in the open. Road impacts may be due to road kills, traffic disturbance and ruptured connectivity.